Preliminary proposal to incorporate new sites for long-term socio-ecological research into the Chilean LTSER network - Donoso, Pablo J; Zavaleta, Jennifer C (BOSQUE, 2017)
Currently Chile belongs to the International Long Term Ecological Research network (ILTER) through three sites: Bosque Fray Jorge National Park, Senda Darwin Biological Station, and Omora Ethnobotanic Park. At the end of 2012 a workshop was held in the Las Animas Cascade Nature Sanctuary with the aim of exploring the potential inclusion of other long-term ecological research sites into the so-called Long-Term Social-Ecological Research sites of Chile (LTSER-Chile). One of the conclusions of this workshop was that it is necessary to know with certain depth what is each site doing in terms of research, education, and outreach. As a consequence, at the beginning of 2013 we conducted a survey to 13 sites, including the three foundational sites and 10 potential sites identified during the workshop. Once received the answers from 12 of the 13 sites, we found that these sites are concentrated mainly in the Valdivian Ecoregion (39-42° S), and the research activities are related mainly to terrestrial ecology and marine ecology in two cases. Almost all sites had activities during the last decade, few sites had long-term research, most sites have conducted outreach activities, but no site had socioecological research. The results show the potential of the sites to extend the LTSER-Chile, but illustrate the need to establish future criteria to belong to the network and the need to include sites in Ecoregions not represented so far.